Analisis Efikasi Diri pada Mahasiswa Psikologi Unimal - Hasnul Mawaddah (Jurnal Psikologi Terapan, 2019)
Self-efficacy is an individual's belief in himself or herself in dealing with or accomplishing a task, to achieve goals, to overcome a problem to achieve a result and one's beliefs about the ability to produce what is desired. Making self-efficacy measuring instrument is expected to help research, examination as well as self-efficacy-related interventions to students. The data retrieval process is taken using a kousioner consisting of manual data retrieval and google form, participants in manual data filling amounted to 33 participants and through google form 57 participants. The subjects of this study were 90 participants consisting of 59 female participants and 31 male participants. The majority of participants are Muslim. Participants come from students who study in Aceh. All participants are unmarried, who are vulnerable aged 18-22. Pursuant to result of psychometric analysis and test done through internal consistency and construct validity test and reliability of self efficacy scale in student have good validity and reliability that is equal to α = 0,819 (81,9%). Measured from 3 components that are sure of ability, have high aspirations and persistence. Out of 40 items made. then the items received after the validity and reliability test are only 20 acceptable items and  15  items fall. With good psychometric standards, the self-efficacy scale described in this study can be used to measure self efficacy in the context of research and psychological intervention, especially in developmental and social psychology.